C1q A08 Is a Half-Cryptic Epitope of Anti-C1q A08 Antibodies in Lupus Nephritis and Important for the Activation of Complement Classical Pathway - Wu, Wen-Jun; Tan, Ying; Liu, Xiao-Ling; Yu, Feng; Zhao, Ming-Hui (Frontiers in Immunology, 2020)
To investigate the fine epitope(s) of anti-C1q A08 antibodies and their role in complement activation in lupus nephritis. Anti-C1q A08 antibodies from ten lupus nephritis patients were purified from plasmapheresis samples and four monoclonal antibodies against C1q A08 were screened and identified from mouse hybridoma cells to study the fine epitope(s) of C1q A08 using ELISA and Biolayer Interferometry (BLI). The biofunction of anti-C1q A08 antibodies for complement classical pathway activation was investigated by C3 activation assay. Anti-C1q A08 antibodies and anti-C1q antibodies were also detected in the sera of female BALB/C mice immunized by C1q A08 peptide. None of the anti-C1q A08 antibodies affinity purified from the ten lupus nephritis patients could bind intact C1q coated on microtitre plates, and the anti-C1q antibodies could not bind to C1q A08 peptide coupled on resin, indicating that the human anti-C1q antibodies and anti-C1q A08 antibodies may recognize different epitopes of C1q. One of the four C1q A08 mAbs (32-4) bound to the six amino acids of N-terminus of C1q A08, while another C1q A08 mAb (17-9) bound to eight or ten amino acids of C-terminus of A08. The third and fourth C1q A08 mAb (1A12 and 4B11) bound to the whole sequence of A08. Only 32-4 mAb bound to intact C1q coating on ELISA plate, while 17-9 mAb, 1A12 mAb and 4B11 mAb could not. However, using BLI assay, 17-9 mAb, 1A12 mAb and 4B11 mAb could bind to intact C1q but 32-4 mAb could not. Furthermore, 1A12 mAb and 4B11 mAb could inhibit the activation of complement classical pathway, while 32-4 and 17-9 mAb could not. Anti-C1q A08 antibodies were detected in all the female BALB/C mice in experimental group but none in the control group. Two out of six in the experimental group developed anti-C1q antibodies. C1q A08 is a half-cryptic epitope of C1q involving N-terminal six amino acids of A08. C1q A08 is important in activation of complement classical pathway and some anti-C1q A08 antibodies were able to prevent this process. Epitope spreading of C1q occurred in mice immunized with C1q A08 peptide.